0405 Patient and Healthcare Provider Surveys of Narcolepsy Disease Burden and Oxybate Treatment Experience. (25th May 2022) - Morse, Anne Marie; Krahn, Lois; Kushida, Clete; Thorpy, Michael; Flygare, Julie; Seiden, David; Athaval, Amod; Gudeman, Jennifer
Abstract: Introduction: Immediate-release sodium oxybate (SXB) and mixed-salt oxybates require patients with narcolepsy to take a second nightly dose 2.5–4 h after the first. Extended-release, once-nightly SXB (ON-SXB; FT218) is an investigational treatment for adults with narcolepsy. Surveys evaluated patient and healthcare provider (HCP) perspectives on narcolepsy disease burden and satisfaction with current narcolepsy treatment options. Methods: Individuals with narcolepsy and HCPs participated in 30-minute, web-based surveys. Participants were 1) adults with self-reported, physician-diagnosed narcolepsy for ≥1 year, and prior/current/no use immediate-release oxybates; and 2) board-certified/board-eligible HCPs (pulmonology, sleep medicine, neurology, psychiatry specialties); nurse practitioners; or physician assistants. Participants responded using 9-point scales; higher scores indicated greater severity/agreement/satisfaction/importance/preference. Results: Mean patient participant (n=120) age was 40 years; most were white (81%), female (79%), and current/past users of twice-nightly SXB (n=86) or mixed-salt oxybates (n=56). Twenty-six were oxybate naive. Most HCPs (n=100; 68% male) had sleep medicine (37%) or neurology (30%) specialties; 91% and 83% had experience with twice-nightly SXB and mixed-salt oxybates, respectively. Patients and HCPs agreed that patients preferred narcolepsy treatments dosed fewer times (rated 6.7 and 7.7, respectively). Common symptoms patients experienced daily/almost daily at narcolepsy diagnosis were tiredness/fatigue (64%) and excessive daytime sleepiness (EDS; 68%). HCPs and patients expressed moderate-to-high satisfaction with mixed-salt oxybates (both 7.1) and twice-nightly SXB (6.8 and 6.6, respectively). Compared to HCPs, patients were less satisfied with modafinil (6.9 vs 4.5), armodafinil (6.9 vs 4.8), solriamfetol (6.8 vs 5.4), and pitolisant (6.6 vs 5.2). Twice-nightly SXB and mixed-salt oxybates received high ratings from patients and HCPs for reduction of cataplexy (patients: 7.3 and 7.4; HCPs, 6.7 and 6.8) and EDS (patients: both 7.0; HCPs, both 6.9). Lower satisfaction was reported for twice-nightly SXB and mixed-salt oxybates with dosing frequency (patients, 5.4 and 6.0; HCPs, 5.9 and 6.3) and medication taste (patients, 5.3 and 5.7; HCPs, 5.9 and 6.2). Conclusion: While both individuals with narcolepsy and HCPs are relatively satisfied with current narcolepsy treatments, both groups are less satisfied with the dosing frequency of currently approved oxybate formulations. ON-SXB will be an additional treatment option that can address this unmet need. Support (If Any): Avadel Pharmaceuticals